'So what do you do?': Third space professionals navigating a Canadian university context. Issue 5 (3rd September 2021) - Smith, Cameron; Holden, Michael; Yu, Eustacia; Hanlon, Patrick
ABSTRACT: Third space professional staff have been emerging as leaders and key contributors to higher education institutions around the world. These staff are employed to support initiatives in such areas as teaching and learning, research management, student services, community engagement, and strategic initiatives, some of which were previously the sole domains of academics. Positioned between these academic and professional spheres, four professionals from the University of Calgary engaged in narrative inquiry to reflect on how their context and lived experiences inform their identities navigating the third space. The authors describe how role ambiguity, self-advocacy, positional liminality, and cross-boundary relationships create challenges and opportunities for third space professionals as they navigate the institution and define their place in it. Implications and suggestions for higher education administrative leaders are provided, based on opportunities for third space professional staff to effectively operate within their organisations.